Appendiceal Neuroendocrine Tumor Is a Rare Cause of Ectopic Adrenocorticotropic Hormone Syndrome With Cyclic Hypercortisolism: A Case Report and Literature Review - Zhao, Yu Xing; Ma, Wan Lu; Jiang, Yan; Zhang, Guan Nan; Wang, Lin Jie; Gong, Feng Ying; Zhu, Hui Juan; Lu, Lin (Frontiers in Endocrinology, 2022)
Objective Ectopic adrenocorticotropic hormone (ACTH) syndrome (EAS) is a condition of hypercortisolism caused by non-pituitary tumors secreting ACTH. Appendiceal neuroendocrine tumor as a rare cause of ectopic ACTH syndrome was reported scarcely. We aimed to report a patient diagnosed with EAS caused by an appendiceal neuroendocrine tumor and summarized characteristics of these similar cases reported before. Case Report and Literature Review We reported a case with Cushing’s syndrome who was misdiagnosed as pituitary ACTH adenoma at first and accepted sella exploration. Serum and urinary cortisol decreased, and symptoms were relieved in the following 4 months after surgery but recurred 6 months after surgery. The abnormal rhythm of plasma cortisol and ACTH presented periodic secretion and seemingly rose significantly after food intake. EAS was diagnosed according to inferior petrosal sinus sampling (IPSS). Appendiceal mass was identified by 68Ga-DOTA-Tyr3-octreotate (DOTATATE)-PET-CT and removed. The pathological result was consistent with appendiceal neuroendocrine tumor with ACTH (+). The literature review demonstrated 7 cases diagnosed with EAS caused by appendiceal neuroendocrine tumor with similarities and differences. Conclusion The diagnosis of an ectopic ACTH-producing tumor caused by the appendiceal neuroendocrine tumor can be a challenging procedure. Periodic ACTH and cortisol secretion may lead to missed diagnosis and misdiagnosis. IPSS is crucial in the diagnosis of EAS and 68Ga-DOTATATE-PET-CT plays an important role in the identification of lesions.